Ecclesiastical jurisdiction in England 1300—1550: the records and their interpretation - Owen, Dorothy Mary (Studies in church history, 1975)
The picture drawn by Chaucer in the Friar’s Tale is a little journalistic, not to say sensational, and it deals with only some aspects of the ecclesiastical jurisdiction of his day, yet it leaves us in no doubt as to the importance of the courts, and of the way in which they were regarded in some quarters. Perhaps the picture was overdrawn, and true only of the half century or so within Chaucer’s own knowledge. On the other hand it has recently been demonstrated that these same courts furnished some at least of the excuses for royal and parliamentary action at the outset of the reformation, and there seems to be good reason for a closer look at them in this context. Most of all, however, for those whose principal interest is the quality of medieval life, it is desirable to consider the institution during the whole period for which there is some sort of continuous record of its working, that is, for the years covered by my title. There is no doubt that such a study should reveal a considerable section of the public and private life of the time, and while in the limits of this paper I can do no more than skim the surface of my material I hope that I shall persuade others to make further and deeper studies.